Hubungan Inisiasi Menyusu Dini Terhadap Pemberian ASI Eksklusif - Rosfiantini, Marlia; Fatmaningrum, Widati; Ningtyas, Woro Setia (Universitas Batanghari Jambi, 2024)
According to the World Health Organization, the gold standard for child nutrition is exclusive breastfeeding. WHO states that babies, mothers and families greatly benefit from exclusive breastfeeding. Even though breastfeeding has many benefits, only twenty percent of mothers in Indonesia exclusively breastfeed. The performance of the hormone prolactin, which produces breast milk, and the hormone oxytocin, which produces breast milk, can influence the success of exclusive breastfeeding. Early initiation of breastfeeding (IMD) is the first step for successful exclusive breastfeeding. The aim of this research is to analyze the relationship between IMD and exclusive breastfeeding in the Mojo Community Health Center Area. This research is observational analytic using a cross sectional research design. The research sample was mothers with babies aged 6 - 12 months who were selected using the purposive sampling method. Data collection through interviews using questionnaires. Data analysis using the Chi Square test and Fisher's Exact Test with α = 0.05. The results of statistical tests show that there is no relationship between IMD and exclusive breastfeeding (p = 0.094), which means that respondents with IMD and without IMD predominantly give exclusive breastfeeding.